2014
DOI: 10.1007/978-3-319-06379-9_14
|View full text |Cite
|
Sign up to set email alerts
|

The Computational Complexity of Density Functional Theory

Abstract: Density functional theory is a successful branch of numerical simulations of quantum systems. While the foundations are rigorously defined, the universal functional must be approximated resulting in a 'semi'-ab initio approach. The search for improved functionals has resulted in hundreds of functionals and remains an active research area. This chapter is concerned with understanding fundamental limitations of any algorithmic approach to approximating the universal functional. The results based on Hamiltonian c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…However, while such a functional exists, it may not be computationally efficient. Indeed, computing it has been shown to be QMA-hard, also under Turing reductions [23]. For both N -representability and DFT, it remains an open question whether they remain hard when the inputs (2-RDMs and electron densities, respectively) are restricted to the ground states of electronic structure Hamiltonians.…”
Section: Formalizing the Electronic Structure Problemmentioning
confidence: 99%
“…However, while such a functional exists, it may not be computationally efficient. Indeed, computing it has been shown to be QMA-hard, also under Turing reductions [23]. For both N -representability and DFT, it remains an open question whether they remain hard when the inputs (2-RDMs and electron densities, respectively) are restricted to the ground states of electronic structure Hamiltonians.…”
Section: Formalizing the Electronic Structure Problemmentioning
confidence: 99%
“…Despite its ability to give finely configured data, DFT is not commonly used in studying nanoscale friction due to the complexity and large time involved in studying interactions between large surfaces. 58 In addition, while DFT most accurately simulates the electronic interactions and friction caused due to it, it may not be used to directly simulate mechanical forces and interactions between atoms, and thus, methods such as MD or MC are required to accurately simulate the process of mechanical wear of a material due to friction. 52 So, DFT, in the context of studying friction, is mostly used to verify theories and models that have been developed using other computational methods and to understand the atomistic mechanisms of the processes being studied.…”
Section: Density Functional Theorymentioning
confidence: 99%
“…Despite the numerous approximations to the universal functional, computational complexity arguments [6,7] showed that obtaining the numerically exact functional is intractable even with quantum computation. It may be possible to obtain a functional using a particular form of the Kohn-Sham orbitals.…”
Section: Introductionmentioning
confidence: 99%